Avaliação ecocardiográfica de pacientes com doença falciforme - Maria Carmen Melo Vasconcelos (2013)
Cardiovascular complications in sickle cell disease (SCD) are common, and have been frequently found nowadays, due to increased longevity of the patients. As a highly informative and reliable method, echocardiography allows an accurate analysis of cardiac morphology and function. Previous studies have focused especially on pulmonar hypertension and its consequence on the rigth-side heart chambers, whereas factors associated with morphological changes in left ventricle (LV) remain poorly understood. The present study was designed to identify clinical, laboratorial and echocardiographic parametes associated with LV remodeling in SCD patients. Methods: ninety consecutive SCD patients, mean age of 28 ± 7 years (range, 18-40 years) without any associated diseases and 20 age- and gender-balanced healthy subjects were enrolled into the study. Standard laboratory tests, 12-lead ECG and a comprehensive echocardiogram with tissue Doppler imaging were performed in all patients. Results: patients with SCD had larger left and rigth heart chambers dimensions, LV mass and tricuspid regurgitation (TR) velocity compared to controls. Despiste chambers enlargement, systolic function of both ventricles was preserved. The mitral inflow velocites were higher in the pacientes than in controls, whereas septal and lateral anular motion velocities were normal, suggesting normal LV relaxation. SCD pacientes who were on hydroxyurea therapy and/or hypertransfusion had higer hemoglobina concentrations, but similar echocardiographic findings in comparison to the individuals without treatment. Systolic blood pressure, ferritin concentration, TR velocity, deceleration time of early mitral inflow velocity, and E/e’ratio were independently associated with increased LV mass. Speckle tracking of both ventricles and atria were not diferent from those of the controls. Conclusions: LV remodeling in SCD pacientes seems to be influenced by a combination of factors including blood pressure, ferritin concentration, TR velocity, and parameters of LV diastolic function. Speckle tracking of both ventricles and atria could not detect any incipiente systolic dysfunction in this group of SCD patients.